PERAN GURU AL-QUR’AN HADIST DALAM MENINGKATKAN MINAT BACA AL-QUR’AN PADA SISWA DI ERA DIGITAL - Afifah, Anisa Nur; Rizal, Ahmad Saiful; Azis, Achmad Abdul (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
This study aims to analyze the role of Qur’an-Hadith teachers in enhancing students’ interest in reading the Qur’an in the digital era at MTs Ma’arif Blora. The dominance of technology and the widespread use of gadgets which often divert students from religious activities serve as a significant background to this research. Using a qualitative approach through interviews, observations, and documentation, the findings reveal that teachers function not only as instructors but also as motivators, mentors, and supervisors of students’ digital behavior. Various strategies are employed to cultivate Qur’anic reading interest, including habituation after the Duha prayer, appreciative assessment of students’ efforts, routine khataman and tahlil activities, the development of boarding school programs, grouping based on reading ability, and personalized guidance using the Yanbu’a and Iqra’ methods. Teachers also collaborate with parents to monitor gadget usage so that digital distractions do not replace the priority of reading the mushaf. The study concludes that fostering Qur’anic reading interest in the digital era requires synergy between teachers, schools, and families, ensuring that technology becomes a medium for strengthening spirituality rather than hindering religiosity. ABSTRAK Penelitian ini bertujuan untuk menganalisis peran guru Al-Qur’an Hadist dalam meningkatkan minat baca Al-Qur’an siswa pada era digital di MTs Ma’arif Blora. Arus teknologi dan dominasi gawai yang cenderung mengalihkan perhatian peserta didik dari aktivitas keagamaan menjadi latar penting penelitian ini. Dengan menggunakan pendekatan kualitatif melalui wawancara, observasi, dan dokumentasi, diperoleh temuan bahwa guru tidak hanya bertindak sebagai penyampai materi, tetapi juga sebagai motivator, pembimbing, dan pengontrol perilaku digital siswa. Berbagai strategi diterapkan untuk menumbuhkan minat baca Al-Qur’an, antara lain pembiasaan membaca setelah shalat dhuha, penilaian apresiatif atas usaha siswa, pelaksanaan khataman dan tahlilan rutin, pengembangan program boarding school, pengelompokan sesuai kemampuan baca, serta pendampingan metode Yanbu’a dan Iqra’. Guru juga menjalin kerja sama dengan orang tua untuk mengawasi penggunaan gawai agar tidak menggeser prioritas membaca mushaf. Hasil penelitian menegaskan bahwa keberhasilan peningkatan minat baca Al-Qur’an pada era digital memerlukan sinergi antara guru, madrasah, dan keluarga, sehingga teknologi dapat diarahkan menjadi sarana penguat spiritualitas, bukan penghalang religiusitas.